2000
DOI: 10.4049/jimmunol.165.7.3541
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Lipopolysaccharide Induces Physical Proximity Between CD14 and Toll-Like Receptor 4 (TLR4) Prior to Nuclear Translocation of NF-κB

Abstract: CD14, a GPI-linked protein, plays a pivotal role in LPS-mediated signaling by potentiating leukocyte adherence, activation, and cytokine production. Recent studies have identified the Toll-like receptor 4 (TLR4) as a membrane cofactor in LPS-mediated transmembrane signaling in cytokine induction, although the mechanism responsible for this cooperation is unknown. Using fluorescence resonance energy transfer (RET) techniques, we demonstrate that LPS triggers a physical association between CD14 and TLR4. Because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
200
1
7

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 297 publications
(220 citation statements)
references
References 29 publications
12
200
1
7
Order By: Relevance
“…Transfer of LPS to CD14 via LBP and a physical association of CD14 with TLR4/MD-2, have been identified as necessary events in the activation of cells such as macrophages by LPS [15,27,28]. The expression of CD14 on MC is still a matter of dispute [29][30][31][32][33][34].…”
Section: Activation Of MC By R-form Lps Is Independent Of Lbp and Cd14mentioning
confidence: 99%
“…Transfer of LPS to CD14 via LBP and a physical association of CD14 with TLR4/MD-2, have been identified as necessary events in the activation of cells such as macrophages by LPS [15,27,28]. The expression of CD14 on MC is still a matter of dispute [29][30][31][32][33][34].…”
Section: Activation Of MC By R-form Lps Is Independent Of Lbp and Cd14mentioning
confidence: 99%
“…Because CD14 is a GPI-anchored protein devoid of a transmembrane domain, by itself, it presumably cannot transmit the activating signal into the cell. Indeed, in vitro work has demonstrated that Toll-like receptor 4 (TLR4) 3 activates the immune system by functioning as a transmembrane coreceptor to CD14 (16,17). Both TLR4-deficient (TLR4 d ) mice and mice with a single point mutation at aa 712 (proline to histidine) in the TLR4 gene (C3H/HeJ) are resistant to the immunostimulatory and pathophysiological effects of LPS (18,19).…”
mentioning
confidence: 99%
“…In addition, it was demonstrated that the physical approximation between CD14 and TLR4 precedes the nuclear translocation of NF-κB and that TLR4 requires CD14 to participate in the process of signaling induced by LPS 41 .…”
Section: Role Of Toll-like Receptor (Tlr4) In the Receptor Complex Ofmentioning
confidence: 99%
“…According to Jiang et al (2000) 41 , there is a physical association of CD14 and TLR4 dependent on LPS. However, the authors did not discern if the binding of LPS triggers a lateral association of these receptors in the plasma membrane or if it occurs during the release of the pre-associated CD14 and TLR4 by an intracellular tool near the membrane.…”
Section: Role Of Toll-like Receptor (Tlr4) In the Receptor Complex Ofmentioning
confidence: 99%
See 1 more Smart Citation